2021
DOI: 10.1101/2021.05.28.446113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cooperativity of catalytic and lectin-like domain ofT. congolensetrans-sialidase modulates its catalytic activity

Abstract: Trans-sialidases (TS) represent a multi-gene family of unusual enzymes, which catalyse the transfer of terminal sialic acids from sialoglycoconjugates to terminal galactose or N-acetylgalactosamine residues of oligosaccharides without the requirement of CMP-Neu5Ac, the activated Sia used by typical sialyltransferases. Most work on trypanosomal TS has been done on enzymatic activities of TS from T. cruzi (causing Chagas disease in Latin America), subspecies of T. brucei, (causing human sleeping sickness in Afri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Similar results were found in single-site N -glycosylation mutants of the IBV spike protein by circular dichroism experiments (5). The observed thermal stability of TconTS1 might be explained by the high β-sheet content of the protein as well as by an extended interface between CD and LD stabilized by salt bridges and a well-structured hydrogen bond network, making unfolding rather unlikely (35). Although N -glycans do not seem to influence the stability of TconTS1 after successful expression, glycans are known to be required for proper protein folding (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in single-site N -glycosylation mutants of the IBV spike protein by circular dichroism experiments (5). The observed thermal stability of TconTS1 might be explained by the high β-sheet content of the protein as well as by an extended interface between CD and LD stabilized by salt bridges and a well-structured hydrogen bond network, making unfolding rather unlikely (35). Although N -glycans do not seem to influence the stability of TconTS1 after successful expression, glycans are known to be required for proper protein folding (3).…”
Section: Discussionmentioning
confidence: 99%
“…Like all TS, TconTS1 consists of an N -terminal catalytic domain (CD) responsible for the transfer of Sia, and of a C-terminal lectin-like domain (LD) whose biological function remains unclear. Recently, we demonstrated that TconTS-LD can modulate enzymatic activity (35). CD and LD are connected via an α-helix (Fig.…”
Section: Introductionmentioning
confidence: 99%